L’inacceptable face aux nécessités politiques : les relations entre censures et raisons d’État à l’époque moderne - Laurie Catteeuw (Les Dossiers du GRIHL)
Reason of State refers to a field of politics governed by rules different from what they are in the ordinary common world: by locating its action at the edge of Law or by departing from it, Reason of State contributes to the creation of new laws which take political requirements into account. In this paper, we aim at understanding its power to change laws over time. In such a perspective, Reason of State appears as allowing what's inacceptable to be transformed through acts that do remain illegal though they adapt themselves to the laws over time. The present paper enlightens the ability of Reason of State to act on the normative power of positive Law by furthering the normalisation of unacceptable practices.